| **Giver** | **Post** | **Date** |

| mndlpz16 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 23-Sep-2023 |

| Alextaller81 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 17-Sep-2023 |

| pooja.sharma2909 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 17-Aug-2023 |

| shwetasood | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 14-Aug-2023 |

| sourovs | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 09-Aug-2023 |

| bernhoudini | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 05-Aug-2023 |

| Khushi1704 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 03-Aug-2023 |

| dmedeiros | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 28-Jul-2023 |

| DivineTyrant | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 24-Jul-2023 |

| Mihika54 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 18-Jul-2023 |

| aditiarvind | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 14-Jul-2023 |

| Anonymoux | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 05-Jul-2023 |

| tran.j51 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 27-Jun-2023 |

| exuberantvivek | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 27-Jun-2023 |

| Nobunaga1337 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 10-Jun-2023 |

| SS.56 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 20-May-2023 |

| Kingkong26 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 15-May-2023 |

| ArnauG | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 06-May-2023 |

| p41060 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 18-Apr-2023 |

| KesRay | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 01-Apr-2023 |

| filpip | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 25-Feb-2023 |

| rcase113 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 15-Feb-2023 |

| vivek1810971 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 04-Feb-2023 |

| aashi007 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 28-Jan-2023 |

| achloes | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 26-Jan-2023 |

| rajatgoyal0794 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 25-Jan-2023 |

| elisa99c | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 18-Jan-2023 |

| rs984 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 21-Dec-2022 |

| BigChungus | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 03-Dec-2022 |

| asarr97 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 31-Oct-2022 |